MAKNA DAN FUNGSI TRADISI SINAMOT DALAM PERNIKAHAN BATAK TOBA DI KECAMATAN MANDAU - Tius, Tommy; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Marriage is one of bind way can do for generation offspring. Legitimate marriage doing performed in accordance with religious law and beliefs it embraces. This research be function for review give process dowry in batak toba marriage system, dowry tradition mean and change dowry mean in Mandau Districs. This research use kualitatif research metode. Source of this data is from interview detail with informan, deservation and documentation. Analysis data technic used in research is data analysis and presentation of data. Finally, dowry tradition in that batak people have dowry tradition and culture batak must be stay run and ptreserved. This tradition has become one of kind from traditional marriage series that validated and approved by batak toba community it self, so can streght social integrity for gentheman batak people and ladies that clan same it mean iboto social ciblings, Batak Toba tribe embraced patrilineal system will be direct work on abstain a son for direct line of descent or clan.Keywords: Sinamot, mahar batak